The Effect of Interactive Media on Students' Mathematical Communication Ability Based on Learning Styles - Sari, Mayang; Choirudin, Choirudin; Hariyanti, Firda; Farooq, Syed Muhammad Yousaf (Delta-Phi: Jurnal Pendidikan Matematika, 2024)
This study aims to examine the effect of interactive media on students' mathematical communication abilities considering different learning styles. Unlike previous research that used a descriptive qualitative method, this study employs a quasi-experimental approach with a pretest-posttest control group design. The participants were seventh-grade students at MTs Ma'arif Roudlotut Tholibin Metro, consisting of six males and ten females with various learning styles. The experimental group was taught using interactive media tailored to their learning styles (visual, auditory, kinesthetic, and read/write), while the control group received traditional instruction. Data were collected through mathematical communication ability tests, learning style questionnaires, and classroom observations. The results showed that students who learned with interactive media had higher mathematical communication abilities compared to those who learned through traditional teaching. Among the learning styles, visual learners benefitted the most from the use of interactive media. These findings suggest that integrating interactive media into mathematics teaching can enhance students' mathematical communication abilities, especially when adapted to their preferential learning styles